Pulmonary eosinophilia associated with carbamazepine. Issue 10 (October 1983) - Tolmie, J; Steer, C R; Edmunds, A T
Abstract : An 8 year old girl treated with carbamazepine developed eczema, wheeze, and evidence of pulmonary eosinophilia. Single dose challenge confirmed allergy to this drug. This reaction should be considered in patients being treated with carbamazepine who develop respiratory symptoms.